Narirutin mitigates neuroinflammation following traumatic brain injury and modulates microglial polarization via the JAK2/STAT3 signaling pathway - Zhang, Hebo; Han, Junming; Yan, Chaolong; Mao, Jiannan; Yan, Huiying; Jin, Wei (Frontiers in Neurology, 2025)
BackgroundTraumatic brain injury (TBI) causes irreversible cerebral damage characterized by neuroinflammation and neuronal injury, representing a critical factor contributing to poor prognosis in TBI patients. While existing studies have demonstrated Narirutin’s (Nar) neuroprotective effects in Parkinson’s disease, research on Nar in the context of traumatic brain injury remains markedly limited. This investigation elucidates Nar’s protective mechanisms in murine TBI models.MethodsThe behavioral tests of TBI model mice were conducted using the Morris water maze method. HE staining, Nissl staining and immunohistochemistry were performed. Western blotting was used to detect inflammatory indicators, and immunofluorescence was used to detect microglial polarization.ResultsNar significantly reduced the inflammatory response and abnormal activation of signaling pathways induced by TBI. This effect is achieved by reducing the expression levels of NLRP3, IL-1β, and IL-6, promoting M2 polarization in microglia, and inhibiting the phosphorylation of JAK and STAT within the TBI model.ConclusionIn conclusion, our research results indicate that Nar can improve neuroinflammation in TBI model mice, demonstrating excellent anti-inflammatory effects and neuroprotective properties, providing potential therapeutic strategies for the clinical treatment of TBI.